Incidence and risk factors of medical device-related pressure injuries among patients undergoing prone position spine surgery in the operating room. Issue 3 (August 2021) - Choi, Mi Ae; Kim, Myoung Soo; Kim, Cheol
Abstract: Aim: We aimed to investigate the incidence rate and risk factors of medical device-related pressure injuries (MDRPIs) among patients undergoing prone position spine surgery. Materials and methods: This was a prospective observational study of 147 patients who underwent spine surgery in an orthopaedic hospital in Korea. The incidence of MDRPI according to intrinsic and extrinsic factors was assessed using the independent t-, χ 2 -, or Fisher's exact tests. A logistic regression analysis was performed exclusively for MDRPI areas with an incidence rate >5%. Results: The mean incidence rate of overall MDRPI was 27.4%, while that of MDRPI by Wilson frame, bi-spectral index, and endotracheal tube (ETT) was 56.5%, 52.4%, and 9.5%, respectively. The risk factors under Wilson frame were operation time and body mass index classification. Compared to their normal weight counterparts, those who were underweight, overweight, and obese had a 46.57(95% CI: 6.37–340.26), 3.96 (95% CI: 1.13–13.86), and 5.60 times (95% CI: 1.62–19.28) higher risk of developing MDRPI, respectively. The risk factors by bi-spectral index were sex, operation time, and the American Society of Anaesthesiologists classification. Compared to ETT intubation of <2 h, the risk of MDRPI increased by 7.16 times (95% CI: 1.35–38.00) and 7.93 times (95% CI: 1.45–43.27) for<3 and ≥3 h' duration, respectively. Conclusion: The difficulty of device repositioning can increase the incidence of MDRPI, and prolonged surgery was a significant risk factor. Thus, appropriate planning and correct equipment utilization is needed during prone position spine surgeries. Highlights: The most significant risk factor for MDRPIs was operation time. Among devices, the Wilson frame is associated with the highest risk for MDRPI. Advanced MDRPIs in the oral mucosa occur earlier than those in the skin.